SOSIALISASI STANDAR OPERASIONAL PROSEDUR (SOP) TATA KELOLA KEPEGAWAIAN DAN ADMINISTRASI UNTUK MENINGKATKAN KINERJA PEGAWAI - Dewi, Yuni Rosita; Setyaasih, Setyaasih; Fitriyani, Zenita Afifah; Ardiyanto, Fahrur Rijal; Putra, Dimas Ganda Permana (LPPM ITB AAS Indonesia Surakarta, 2024)
Standard Operating Procedures (SOP) are something that use to overcome resource quality problems. At Mayjen Sungkono University, there is a Quality Assurance Board, one of which is ensuring quality through standards set by the relevant ministry and standards set internally. To measure the level of success of the established SOP, community service activities are carried out in the form of outreach. As for problems related to the quality of resources, socialization of Standard Operating Procedures (SOP) related to governance such as Personnel, Finance, Administration and Infrastructure was held. The resource person for this socialization is the Quality Assurance Board together with the Vice Rector II who is in charge of personnel, finance, administration and infrastructure. The targets of this socialization in community service are leaders, lecturers and education staff. The evaluation results from this socialization were that three of the four indicators had increased (75%). So, the goal of community service was achieved through changes in the attitudes and administration of the Mayjen Sungkono University academic community after socialization was carried out. Quality improvement continues to be carried out with future SOPs related to administration and finance as well as infrastructure for students, especially those participating in the Student Activity Unit (UKM) and Student Executive Board (BEM).